Functional genomics lead to new therapies in follicular lymphoma. (15th May 2013) - Oricchio, Elisa; Wendel, Hans‐Guido
Abstract : Recent technological advances allow analysis of genomic changes in cancer in unprecedented detail. The next challenge is to prioritize the multitude of genetic aberrations found and identify therapeutic opportunities. We recently completed a study that illustrates the use of unbiased genetic screens and murine cancer models to find therapeutic targets among complex genomic data. We genetically dissected the common deletion of chromosome 6q and identified the ephrin receptor A7 ( EPHA7 ) as a tumor suppressor in lymphoma. Notably, EPHA7 encodes a soluble splice variant that acts as an extrinsic tumor suppressor. Accordingly, we developed an antibody‐based strategy to specifically deliver EPHA7 back to tumors that have lost this gene. Recent sequencing studies have implicated EPHA7 in lung cancer and other tumors, suggesting a broader therapeutic potential for antibody‐mediated delivery of this tumor suppressor for cancer therapy. Together, our comprehensive approach provides new insights into cancer biology and may directly lead to the development of new cancer therapies.